A apatridia e a ressignificação do pertencimento ao Estado-Nação: o caso dos Roma na Itália - Ferreira, Amanda (2019)
Statelessness is defined by the absence of the nationality legally recognized by an State and, in this sense, is directly related with the notion of sovereignty, an important concept widely discussed in Political Science field and with distinct emphasis in the studies of International Relations. Our goal in this dissertation is to observe statelessness from an approach that understands it as a phenomenon that conforms, at the same time, aspects of control, negotiation and resistance, taking as object of analysis the case of the Roma people in Italy and, more specifically, the question of the so-called “nomad camps” in the country. The work will be based on a theoretical debate about how statelessness is intimately related to the concept of sovereignty and how this, from an approach of security and biopolitics anchored in the work of Foucault, Agamben and Arendt, is fundamental to the comprehension of the materialization of statelessness and the dynamic of the camps as phenomena that project itself as depolarizing and excluding, but that open slits for a re-signification of the idea of belonging and political participation